Numerical Study on Heat Transfer and Enhancement Mechanism in PCM-Filled Shell-and-Tube Heat Exchangers - Fang, Jiabin; Han, Tao; Bi, Yixin; Yan, Haobing; Wei, Jinjia (Frontiers in Energy Research, 2022)
A numerical model was established using the enthalpy-porosity approach to study the heat transfer characteristics of a shell-and-tube phase change heat exchanger filled with paraffin wax RT50. The influence of exchanger placement forms, tube diameters and fin structures on the phase change process of RT50 was analyzed. The results depicted that the vertical heat exchanger has a faster melting rate than the horizontal one as the tube diameter is large. However, the opposite results were obtained in case the tube diameter is small. For the horizontal exchanger, the heat conduction is dominant at the beginning and end of the melting process, while the natural convection plays a more important role at the intermediate stage of melting. Besides, the duration of the melting is mainly determined by the natural convection. In addition, adopting fins on the outer of the tube can significantly improve the heat transfer and therefore shorten the melting time. Compared with finless tube, the use of annular-fin tube can reduce the melting time by 31.6% mainly because of the intensifying of heat conduction, while the use of straight-fin tube can shorten the melting time by 42.1% attributed to the enhancement of both natural convection and heat conduction during the melting process.